Performance optimisation of solid oxide electrolyser cell (SOEC) using response surface method (RSM) for thermal gradient reduction - Syafawati Hasbi; Ityona Amber; Mamdud Hossain; Mohd Shahneel Saharudin (International Journal of Sustainable Energy)
The Solid Oxide Electrolyser Cell (SOEC) offers high-efficiency hydrogen production due to favourable thermodynamics and reaction kinetics at elevated temperatures. However, high operating temperatures increase energy consumption and thermal gradients, leading to material degradation and reduced durability. This study optimises SOEC operating conditions to minimise thermal gradients and enhance performance using numerical simulations and Response Surface Methodology (RSM). Key parameters examined include voltage (1.1–1.5 V), temperature (1073–1273 K), steam mass fraction (0.3–0.9), flow configurations, porosity, and charge transfer coefficients. Results show increasing voltage from 1.1 to 1.5 V raised current density from 0.75 A/cm² to 2.5 A/cm², while thermal gradients increased up to 15 K at higher temperatures. Counterflow configurations caused mid-cell hotspots, whereas parallel flow produced thermal gradient near the outlet. RSM optimisation identified optimal conditions of 1073, 1.5 V, and 0.9 steam mass fraction, reducing hotspot temperatures to 1086 K with minimal deviation. These findings support improved SOEC thermal management and hydrogen production efficiency.